Hadron structure functions at small x from string theory - Koile, Leandro Ezequiel (2015)
Deep inelastic scattering of leptons from hadrons at small values of the Bjorken parameter x is studied from superstring theory. In particular, we focus on single-flavored scalar and vector mesons in the large N limit. This is studied in terms of different holographic dual models with flavor Dp-branes in type IIA and type IIB superstring theories, in the strong coupling limit of the corresponding dual gauge theories. We derive the hadronic tensor and the structure functions for scalar and polarized vector mesons. In particular, for polarized vector mesons we obtain the eight structure functions at small values of the Bjorken parameter. The main result is that we obtain new relations of the Callan-Gross type for several structure functions. These relations have similarities for all different Dp-brane models that we consider. This would suggest their universal character, and therefore, it is possible that they hold for strongly coupled QCD in the large N limit.